The Relationship of Self Forgiveness with Well Being Psychology in Female Prisoners in Banyuwangi Correctional Facility in 2024: INDONESIA - Ervia Toga; Fransiska Erna Damayanti; Wiwin Tri Lestari (PT ARRUS Intelektual Indonesia, 2025)
Female inmates often face intense emotional stress due to guilt, shame, and social stigma for the actions they have committed. Continuous emotional stress will affect the psychological well-being of inmates. If inmates have poor psychological well-being, it will affect their productivity. Psychological well-being in inmates can be improved by applying the concept of self-forgiveness. This study aimed to determine the relationship between self-forgiveness and psychological well-being in female inmates. This study is a quantitative correlative study with a cross-sectional approach. The sample used was 45 female inmates selected using the total sampling method. The independent variable in this study is self-forgiveness, and the dependent variable is psychological well-being. The instruments used were the Heartland Forgiveness Scale (HFS) and Psychological Well-Being Scale (PWBS) questionnaires. The collected data were then analyzed using Spearman Rank in IBM SPSS Statistics v.26. The respondents' levels of self-forgiveness and psychological well-being and 27 (60.0%) respondents of the Spearman Rank analysis showed a Sig. (2-tailed) value of 0.045 (<0.05), meaning there is a significant relationship between self-forgiveness and psychological well-being in female inmates in Banyuwangi Prison. The results of this study have important implications for prisoner rehabilitation programs. Interventions focusing on increasing self-forgiveness, such as gratitude or empathy-based counseling and therapy, can help inmates achieve better psychological well-being.